2010
DOI: 10.1016/j.ejphar.2010.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a synthetic protease inhibitor (gabexate mesilate) and a neutrophil elastase inhibitor (sivelestat sodium) on acid-induced lung injury in rats

Abstract: The present study was designed to examine the combined effects of a synthetic protease inhibitor (gabexate mesilate) with a specific neutrophil elastase inhibitor (sivelestat sodium) on acid-induced lung injury. Adult male Sprague-Daley rats weighing 300-350 g were anesthetized intraperitoneally with pentobarbital sodium and the right jugular vein was cannulated. Following tracheostomy, rats were ventilated mechanically and underwent intratracheal instillation of hydrochloric acid (HCl, 0.1N 1.5 ml/kg) or norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In the present study, we found that therapeutic treatment of sivelestat, a small molecular weight inhibitor of neutrophil elastase, exhibited protective effects against LPS-induced lung injury. In agreement with our findings, previous studies have reported the protective effects of sivelestat against ALI/ARDS caused by other stimuli such as acid aspiration [29], mechanical ventilation [30], hemorrhagic shock [31], and hyperoxia [32]. Taken together, these findings support the idea that neutrophil elastase plays an important role in the pathogenesis of ALI/ ARDS.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we found that therapeutic treatment of sivelestat, a small molecular weight inhibitor of neutrophil elastase, exhibited protective effects against LPS-induced lung injury. In agreement with our findings, previous studies have reported the protective effects of sivelestat against ALI/ARDS caused by other stimuli such as acid aspiration [29], mechanical ventilation [30], hemorrhagic shock [31], and hyperoxia [32]. Taken together, these findings support the idea that neutrophil elastase plays an important role in the pathogenesis of ALI/ ARDS.…”
Section: Discussionsupporting
confidence: 82%
“…NE is a protease capable of degrading multiple protein targets, including extracellular matrix proteins such as elastin, collagen and fibronectin, which are abundant proteins of the alveolar basement membrane. NE inhibitors, e.g., sivelestat sodium (ONO Pharmaceuticals), have been evaluated in clinical trials in patients with COPD (Hayakawa et al, 2010;Morjaria et al, 2010), and in acute lung injury patients (Yoshikawa et al, 2010). The use of sivelestat together with oseltamivir effectively reduced lung injury in a patient infected with the 2009 pandemic swine-influenza virus (Yokoyama et al, 2010).…”
Section: Inhibitors Of Neutrophil Proteasesmentioning
confidence: 99%
“…The HNE acylating agent par excellence continues to be Sivelestat (Elaspol R ) (Figure 4) (89), marketed in Japan and Korea for the treatment of acute lung injury associated with systemic inflammatory response syndrome and is currently explored for a range of other indications, including sepsis associated with acute respiratory distress syndrome and disseminated intravascular coagulation (9092). …”
Section: Hne Inhibitorsmentioning
confidence: 99%